Evaluation of ciliary cleft changes after phacoemulsification using ultrasound biomicroscopy in dogs with cataracts - Kim, Donghee; Goh, Yeong-Seok; Kim, Hyemin; Park, Sang-Eun; Hwang, Jiyi; Kang, Nanyoung; Jung, Ji Seung; Park, Kyung-Mee (Frontiers in Veterinary Science, 2023)
Glaucoma is one of the most serious complications that causes irreversible blindness after phacoemulsification in dogs; however, a clear mechanism has not been elucidated. This study aimed to analyse the possible anatomical factors associated with glaucoma after phacoemulsification using parameters that reflect the anatomical characteristics of dogs. A total of 69 eyes of 48 dogs were included in this study. The patients were divided into three groups: normal eye (n=18), cataract (n=39), and post-phacoemulsification for at least two months after surgery (post-phaco, n=12). For further analysis, the dogs were subdivided into two groups according to cataract stage: phacoemulsification non-candidate and candidate groups. Non-cataracts and incipient cataracts were categorised into the non-candidate group, whereas immature and mature cataracts were categorised into the candidate group. Measurements of the ciliary cleft parameters, including the area of the ciliary cleft (CCA), length of the ciliary cleft (CCL), width of the ciliary cleft (CCW), iridocorneal angle, and angle opening distance, were obtained using ultrasound biomicroscopy. CCA, CCL, and CCW were significantly higher in the candidate group than in the non-candidate group. CCA, CCL, and CCW were significantly reduced in the post-phaco group compared to those in the cataract group. Based on these results, we found that the ciliary cleft expanded in cataract-affected eyes and narrowed after phacoemulsification. This may indicate that the space between the trabecular meshworks became narrower, potentially leading to an increase in the resistance of the aqueous humour. Consequently, a narrowed ciliary cleft after phacoemulsification may be an anatomical factor associated with glaucoma.